Pengaruh Fitur Live Streaming dan Flash Sale Tiktok Shop terhadap Keputusan Pembelian Produk Kosmetik Merek Maybelline: Studi Kasus pada Mahasiswi Manajemen Angkatan 2022 - Bertitin Sule Sampe (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2025)
This study aims to analyze the influence of the Live Streaming and Flash Sale features on TikTok Shop on purchasing decisions for Maybelline cosmetic products. The research employs a quantitative approach using a survey method, with a questionnaire distributed to 79 female students of the 2022 Management Program at the Faculty of Economics, Universitas Kristen Indonesia Toraja. Based on the analysis results, it was found that the Live Streaming feature has a positive and significant impact on purchasing decisions, while Flash Sale does not show a significant effect. Simultaneously, both variables have a significant effect on purchasing decisions, with an R² value of 15.1%. This indicates that other factors outside of the variables studied influence purchasing decisions by 84.9%. The findings suggest that the Live Streaming feature is more effective in influencing purchasing decisions compared to Flash Sale, highlighting the importance of utilizing interactive and real-time features to enhance consumer purchase intent on e-commerce platforms like TikTok Shop. This study provides insights for marketers in designing more targeted digital marketing strategies on social media platforms.